2017
DOI: 10.1103/physrevb.95.155207
|View full text |Cite
|
Sign up to set email alerts
|

Density-dependent exciton dynamics and L -valley anisotropy in germanium

Abstract: Optical pump-THz probe spectroscopy is used to investigate the exciton formation dynamics and its intensity dependence in bulk Ge. Associated with the intra-excitonic 1s-2p transition, the gradual build-up of an absorption peak around 3.1 meV (0.75 THz) signifies the delayed exciton formation after optical pump which is accelerated for higher excitation densities. Analyzing the spectral shape of this THz absorption resonance, two distinct resonances are found which are attributed to the mass-anisotropy of L va… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Via the optical excitation of the Ge sample by an ultrashort optical pulse with a central photon energy of 0.8 eV, we create an unbound electron-hole plasma. On a timescale of several ns, this plasma condenses into bound electron-hole pairs as discussed in detail in [10]. This configuration is the initial condition for the THz probe pulse which has a 9 ns delay and a low field strength of 0.12 kV cm −1 .…”
Section: Results and Analysismentioning
confidence: 94%
See 3 more Smart Citations
“…Via the optical excitation of the Ge sample by an ultrashort optical pulse with a central photon energy of 0.8 eV, we create an unbound electron-hole plasma. On a timescale of several ns, this plasma condenses into bound electron-hole pairs as discussed in detail in [10]. This configuration is the initial condition for the THz probe pulse which has a 9 ns delay and a low field strength of 0.12 kV cm −1 .…”
Section: Results and Analysismentioning
confidence: 94%
“…We use an excitation density of 8.3×10 13 photons cm −2 . For the THz pulses, we choose a delay of 9 ns since previous experiments [10] have shown that at those experimental conditions an almost pure incoherent population of 1s-excitons has formed. The THz pulses are generated using a LT-grown large aperture GaAs antenna that is excited by the fundamental laser pulse emitted by the femtosecond amplifier system, which delivers pulses with a duration of 35 fs and a central energy of 1.55 eV (800 nm).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…THz spectroscopy evolved from an exotic technique two decades ago to a widely used and commercially available method, [199] covering the far-IR spectral range between approximately 3-300 wavenumbers, which corresponds to the frequency range of about 0.1-10 THz. Among others, Martin Koch and his group (Philipps-Universität Marburg) demonstrated that THz spectroscopy is not only used for basic research, for instance to study fundamental physical mechanisms such as the formation and decay of excitons [200,201] (in the fashion of previous exciton formation studies [202] ) or the formation of crystals out of a solution, [203] but also for non-destructive testing. Recently, Stuebling et al combined a THz system with a robotic arm to achieve and demonstrate a THz tomography apparatus for the analysis of arbitrarily shaped samples.…”
Section: Nanoscale Systems and Characterization Techniquesmentioning
confidence: 99%